A rapid road to employment? The impacts of a bus rapid transit system in Lima - Lynn Scholl; Daniel Martinez; Oscar A. Mitnik; Daniel Oviedo; Patricia Ya\~nez-Pagans (Inter-American Development Bank (IDB), 2018)
Despite the growing interest in and proliferation of Bus Rapid Transit (BRT) systems around the world, their causal impacts on labor market outcomes remain unexplored. Reduced travel times for those who live near BRT stations or near feeder lines, may increase access to a wider array of job opportunities, potentially leading to increased rates of employment, access to higher quality (or formal) jobs, and increased labor hours and earnings. This paper assesses the effects of the Metropolitano, a BRT system in Lima (Peru), on individual-level job market outcomes. We rely on a difference-in-differences empirical strategy, based on comparing individuals who live close to the BRT system with a comparison group that lives farther from the system, before and after the system started to operate. We find large impacts on employment, hours worked and labor earnings for those individuals close to the BRT stations, but not for those who live close to the feeder lines. Despite the potential to connect poor populations, we find no evidence of impacts for populations living in lower income areas.
Keywords: J01; J21; O12; R40; 330; Bus Rapid Transit; employment; impact evaluation